Hubungan antara Family Dysfunction dengan Kesejahteraan Psikologis Mahasiswa di Jakarta - Adinda Zahra Septiany Rusdiono; Yuarini Wahyu Pertiwi; Wahyu Aulizalsini Alurmei (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
Psychological well-being is a fundamental indicator in supporting the optimal development of university students as emerging adults. One factor that is believed to be significantly associated with psychological well-being is family dysfunction, a dysfunctional condition within the family system characterized by the family's inability to adequately perform its essential functions, including communication, problem-solving, and the provision of emotional support. This study aimed to examine the relationship between family dysfunction and psychological well-being among university students in Jakarta. The study employed a quantitative approach with a correlational research design. The sample consisted of 100 active university students who resided in or were pursuing their studies in Jakarta, selected using a purposive sampling technique. Data were collected using the Indonesian Family Function Scale (IFFS) to measure family dysfunction and the Ryff Psychological Well-Being Scale (RPWBS) to assess psychological well-being. Data were analyzed using Spearman's rank-order correlation through JASP software. The results revealed a strong and statistically significant negative relationship between family dysfunction and psychological well-being (? = ?0.640, p < .001). These findings indicate that higher levels of family dysfunction are associated with lower levels of psychological well-being among university students. This study is expected to contribute to the development of family psychology research and provide an empirical foundation for mental health promotion programs targeting university students through the strengthening of family functioning.